Nonexistence of some T-factorizations of order 12 - Petrenyuk, A. Ya. (Ukrains’kyi Matematychnyi Zhurnal, 2006)
We investigate the Beineke problem of the existence of T-factorizations of complete graphs and prove several theorems on the existence of T-factorizations. Using these theorems, we establish the nonexistence of T-factorizations for 32 nonisomorphic admissible trees of order 12.